G410(P) Viral Infections on the neonatal unit: Their impact on the care of newborns. (27th April 2016) - Vreugde, M; Gresley, J; Timms, J; Nath, P; Satodia, P
Abstract : Aim: To determine the prevalence of viral infections in neonates admitted to the intensive care unit and assess their impact on the escalation/duration of respiratory support, the total length of stay, and mortality. Method: We conducted a retrospective cohort study over a 5-year period (01/01/2010–31/12/2014) of neonates admitted to the neonatal intensive care unit at a regional tertiary neonatal unit. All neonates with any bodily fluid sample sent to pathology for viral testing were included. Mann-Whitney U test was used to compare the means and the results were confirmed via logistic regression using SPSS version 22. Ethical approval was obtained from the local ethics board. Results: Over the 5-year period 2, 934 patients were admitted. 641 babies had virology samples tested. Of 641 babies, 43 babies were positive for 52 viruses. The overall prevalence of viral infections was 1.47% for all admissions and 6.7% in babies with clinically suspected viral infections. The most common virus was rhinovirus (n = 15) followed by parainfluenza (n = 5), adenovirus (n = 5), rotavirus (n = 5), cytomegalovirus (n = 5), respiratory syncytial virus (n = 4), norovirus (n = 4), enterovirus (n = 4), influenza (n = 2), herpes simplex virus (n = 2), and metapneumovirus (n = 1). The length of stay significantly increased in the 23–27 week gestational age group neonates with viral infections compared to neonates without viral infections (85.3 days vs. 57.7, p = 0.002). Days spent on low-flow oxygen significantly increased in the 28–32 week gestational age group with viruses (12.9 vs. 5.9 days, p = 0.007). Babies born after 38 weeks with viral infections were significantly more often discharged with home oxygen (40% vs 3.2%, p = 0.001) Viral infections were associated with higher rates of patent ductus arteriosus (p = 0.006) and respiratory distress (p = 0.006). There was a trend showing increase in ventilation days however this was not statistically significant. No difference was noted with regards to mortality. Conclusion: Neonates who tested positive for viruses had longer durations of stay, increased risk of developing infections, spent more days on respiratory support and had an increased probability of getting discharged on home oxygen.